INTEGRATING LOCAL CULTURE TO PROMOTE CHARACTER EDUCATION IN TEACHING WRITING - Fenny Thresia (Premise: Journal of English Education and Applied Linguistics, 2015)
Abstract :Character educationplays an important partbecause it isnot onlyabout moralandvalueeducation. It has ahighersignificanceofmoraleducation, because itnot onlyteacheswhat is rightand what iswrong. More than thatcharacter educationinculcate the habit(habituation) aboutgood thingsandwrong, canfeel(affective domain) good valueandused to do(behaviouraldomain).So the character education linked closely associated with persistent habits practiced or implemented. It is commonly believed that the practices of English language teaching always accompanied by the insertion of foreign cultural values which are not always in line with Indonesia cultural values. The aim of this study is to improve students’ writing skill through integrating local culture material. Therefore this study focuses on designing and evaluating teaching writing material for English department students of University Muhammadiyah Metro. The result of this study shows that students have big interest and motivation in writing a text based on their local culture. The students also get moral value and character building through the material. It influences the students’ character in their daily life. Students become more polite, honest, diligent and religious.                                                                                                                                           Keywords: local culture, character education, writing.